Using idle TDMA slots for retransmitting packets cooperatively in VANET - Zhen CHEN; Jiang-hong HAN; Yong YANG; Zheng-yu LIU; Yang LU (Tongxin xuebao)
The distributed TDMA approach for VANET dose not take advantage of idle slots,failing to effectively utilize radio resources.A retransmission method for medium access control was proposed for utilizing idle slots.In the method,neighboring nodes utilized idle slots for retransmitting a packet which failed to reach the target receiver.Theoretical analysis and simulation results show that the proposed method significantly increases the probability of successful packet transmission and the network throughput.In addition,a comparison between the proposed method and IEEE 802.11p was presented via extensive simulation,and the results prove that,due to its ability to access channel determinately,the method can disseminate real-time safety information timely and stably.